La minería de procesos, una tecnología para automatizar la gestión de procesos de negocio (2016)
When focusing on business processes, organizations warned that managing these processes was no simple task. With the goal of supporting the management of these business processes, Process Mining has emerged as a technology that allows the automatic analysis and improvement of processes.  The benefits of Process Mining are great, but many organizations -especially en Latin America- do not know about or do not use this technology. In order to reduce this lack of knowledge, this article presents real cases of the application of this technology, as well as their positive results.  Furthermore, it provides improvements to a specialized Process Mining technique for identifying the source of failures in business processes.  It has been possible to demonstrate the advantages of applying Process Mining in diverse organizations, as well as the implemented improvements in the technique for identifying failures.